State of the art of semi-analytic models - Cora, Sofía Alejandra (2011)
Semi-analytic models of galaxy formation and evolution are a powerful method to study how galaxies form and evolve within individual dark matter halos in a Λ-CDM cosmogony. We present the state of the art of current semi-analytic models, focusing on those properties of the galaxy population that are not properly reproduced by the model, which give hints of the astrophysical processes that still need better understanding.